2004
DOI: 10.1074/jbc.m313870200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of QacR-Diamidine Complexes Reveal Additional Multidrug-binding Modes and a Novel Mechanism of Drug Charge Neutralization

Abstract: The Staphylococcus aureus multidrug-binding protein QacR represses transcription of the plasmid-encoded membrane protein QacA, a multidrug efflux transporter. QacR is induced by multiple structurally dissimilar monovalent and bivalent cationic lipophilic compounds, many of which are effluxed from the cell by QacA via the proton motive force. The multidrug-binding pocket of QacR has been shown to be quite extensive and features several glutamates and multiple aromatic residues. To date, the structure of only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
96
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 31 publications
(36 reference statements)
11
96
0
Order By: Relevance
“…4). A similar duality (complementary between hydrophobic and polar interactions) was observed for the binding of effector molecules to other multidrug binding regulators such as BmrR (22) and QacR (23,24) and might represent a general feature for multidrug recognition by this class of proteins.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…4). A similar duality (complementary between hydrophobic and polar interactions) was observed for the binding of effector molecules to other multidrug binding regulators such as BmrR (22) and QacR (23,24) and might represent a general feature for multidrug recognition by this class of proteins.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, a number of studies have shown that the expression of some MDR transporters is controlled by transcriptional regulators with the same multidrug recognition properties, such as BmrR of Bacillus subtilis (18), EmrR of E. coli (19), QacR of Staphylococcus aureus (20), and TtgR of Pseudomonas putida DOT-T1E (21). In that sense, the recent determination of the three-dimensional structures of QacR and BmrR in complex with several ligands has provided important insight into the molecular mechanism of multiple drug recognition (22)(23)(24).…”
mentioning
confidence: 99%
“…Similar drug-regulator interaction has been found in QacR, in which the QacR regulator neutralized one end of the positively charged pentamidine by using carbonyl and side chain oxygen atoms. 27 Interestingly, the bound Chd rather employed another mechanism to neutralize its formal negative charge, whereas the anionic pentanoate group was compensated by the formal positive charge of H174.…”
Section: Discussionmentioning
confidence: 99%
“…Gly-313 has also been identified as a functionally important residue that appears to assume a structurally important role common to the transport process. Furthermore, mutagenic studies clearly demonstrate the multifaceted nature and flexibility of the multidrugbinding sites that can easily adapt to modifications and that appear to be a common trend among multidrug-binding proteins (42)(43)(44)(45)(46). …”
Section: Discussionmentioning
confidence: 99%